Is Private Production of Hospital Services Cheaper than Public Production? A Meta-Regression of Public Versus Private Costs and Efficiency for Hospitals. Issue 1 (2nd January 2020) - Bel, GermÀ; Esteve, Marc
ABSTRACT: The question of whether private organizations can outperform public ones in public service delivery has been a major topic of interest over the last few decades. However, the empirical evidence does not systematically support the hypothesis of lower costs and higher efficiency when private organizations deliver public services. To better understand the cost and efficiency differences between public and private organizations, we have conducted a meta-regression analysis of econometric studies relating to hospital ownership and performance. We have analyzed 61 estimates extracted from health studies, using public versus private hospital costs and efficiency as an independent variable. Our analysis shows a genuine true effect in favor of public sector hospitals. Although we found evidence that the public sector may provide public health services more cheaply than the private sector, the latter achieves better productive efficiency. We discuss how this divergence in results is affected by factors such as country, year, the use of panel data in a study, the extent to which performance is measured by examining financial costs, and the inclusion of not-for-profit hospitals.